Theoretical principles of cloud-based pedagogical environment design for primary school teachers' training - N. V. Bakhmat (Academy of Cognitive and Natural Sciences, 2015)
Research goals: the theoretical principles of planning cloud based environment design of higher pedagogical educational establishment. Research objectives: to study the level of investigation of theoretical principles of cloud based pedagogical environment design for primary school teachers' training in scientific and methodological literature, to reveal its main point, structural elements, functions, and expedience of creation, to account the tendency of progress of informative society of pedagogical education in highly developed countries while planning the innovative environment. The object of research is the process of pedagogical training of primary school teachers, the subject is the theoretical principles of cloud based pedagogical environment design for primary school teachers' training. In accordance with the purpose and tasks of the research the followings methods are used: retrospective-comparative, logic analysis of pedagogical literature, dissertations, generalization, and theoretical planning. The results of empiric analysis of the state of research of the problem of forming the theoretical principles of cloud based pedagogical environment design for primary school teachers' training prove that there is a necessity of search of non-standard ways of solving the pedagogical tasks related to the pupils' education, which are impossible to solve by the help of traditional ways. This process requires the formation of certain demands to professional and personal qualities of a modern teacher. It is connected with the search of new approaches and forming of innovative organization conditions of pedagogical training of primary school teachers in higher pedagogical educational establishments. The research of the process of pedagogical preparation of primary school teachers and the process of informatization of higher and school education, defining the ways of forming the competitiveness in the process of teaching pedagogics in higher educational establishments require the detailed theoretic and methodological study. The main conclusions and recommendations. The marked above specifies on the necessity of the search and forming of the innovative models of pedagogical training of primary school teachers, the aim of which is the orientation on free development of subjects of educational process, free choice of own conception of professional activity by future teachers under the conditions of innovative cloud based pedagogical educational environment.